Respuesta :
Answer:
-7
Step-by-step explanation:
-1.68j+1.24=13
-1.68j=13-1.24
-1.68j=11.76
j=11.76/-1.68
j=-7
Hi there! Hopefully this helps!
-----------------------------------------------------------------------------------------------------------
Answer: j = -7
You can also rewrite the equation(replace "j" with the answer):
-1.68(-7) + 1.24 = 13.
~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
How I solved it:
-1.68j + 1.24 = 13.
We subtract 1.24 from both sides.
-1.68j = 13 - 1.24
~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
-1.68j = 13 - 1.24
We subtract 1.24 from 13 to get 11.76.
-1.68j = 11.76
~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
-1.68j = 11.76
We then divide both sides by -1.68.
j = [tex]\frac{11.76}{-1.68}[/tex]
~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
Expand [tex]\frac{11.76}{-1.68}[/tex] ≈ -7 by multiplying both the numerator and the denominator by 100.
j = [tex]\frac{1176}{-168}[/tex]
~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
Divide 1176 by -168 to get -7.